السر المهني في أداء الوظيفة العمومية بالجزائر - محمد شيكوش اسمهان - ا - بلعمري دليلة (جامعة المسيلة, 2024)
هدفت هذه الدراسة إلى: - تحليل مفهوم السر المهني في التشريع الج ازئري وفهم مدى تأثيره على أداء الوظائف العامة. - فهم اآلليات واألنظمة الموجودة في التشريع الج ازئري لحماية السر المهني وضمان سالمته. - استكشاف التحديات والمعوقات التي يواجهها العاملون في القطاع العام في الحفاظ على السر المهني وكيفية التعامل معها. - دراسة تأثير احترام السر المهني على فعالية وكفاءة العمل في المؤسسات العمومية في الجزائر. كما تم الخروج بمجموعة من النتائج منها: - من خالل االلتزام بالسر المهني يتم تعزيز النزاهة والثقة بين المواطنين واإلدارة العمومية، مما يعزز من فعالية العمل في المؤسسة العمومية ويؤدي إلى تحسين صورة اإلدارة العامة في نظر الجمهور. - يضمن االلت ازم بالسر المهني حماية المعلومات الشخصية والحساسة التي تتعامل معها اإلدا ارت العمومية، مما يحمي حقوق األف ارد ويمنع إساءة استخدام هذه المعلومات. - االلتزام بالسر المهني هو واجب قانوني مفروض على الموظفين العموميين بموجب القوانين واألوامر والمراسيم المعمول بها في الجزائر، كما أنه التزام أخالقي يهدف إلى تعزيز مهنية وكفاءة الموظف العمومي. الكلمات المفتاحية: التشريع الج ازئري، اإلدارة العمومية، الموظف العام، السر المهني. Abstract : This study aimed to: - Analyze the concept of professional secrecy in Algerian legislation and understand its impact on the performance of public functions. - Understand the mechanisms and systems in Algerian legislation that protect professional secrecy and ensure its integrity. - Explore the challenges and obstacles faced by public sector workers in maintaining professional secrecy and how to address them. - Examine the impact of respecting professional secrecy on the effectiveness and efficiency of work in public institutions in Algeria. The study yielded several findings, including: - By adhering to professional secrecy, integrity and trust between citizens and public administration are enhanced, which improves the effectiveness of work in public institutions and enhances the public image of the administration. - Adherence to professional secrecy ensures the protection of personal and sensitive information handled by public administrations, safeguarding individual rights and preventing the misuse of such information. - Adherence to professional secrecy is a legal duty imposed on public employees by the laws, orders, and decrees in force in Algeria. It is also an ethical commitment aimed at enhancing the professionalism and efficiency of public employees. Keywords: Algerian legislation, public administration, public employee, professional secrecy.
Keywords: التشريع الج ازئري، اإلدارة العمومية، الموظف العام، السر المهني.